Exploring the Scope of Tandem Palladium and Isothiourea Relay Catalysis for the Synthesis of α-Amino Acid Derivatives - Jacqueline Bitai; Alexandra M. Z. Slawin; David B. Cordes; Andrew D. Smith (Molecules, 2020)
The scope and limitations of a tandem N-allylation/[2,3]-rearrangement protocol are investigated through the incorporation of a variety of functional groups within an allylic phosphate precursor. This method uses readily accessible N,N-dimethylglycine aryl esters and functionalized allylic phosphates, forming quaternary ammonium salts in situ in the presence of a palladium catalyst. Subsequent enantioselective [2,3]-sigmatropic rearrangement, promoted by the chiral isothiourea tetramisole, generates α-amino acid derivatives with two contiguous stereocenters. The incorporation of electron-withdrawing ester and amide groups gave the best results, furnishing the desired products in moderate to good yields (29–70%), with low diastereocontrol (typically 60:40 dr) but high enantioselectivity (up to 90:10 er). These results indicate that substrate–catalyst interactions in the proposed transition state are sensitive to the substitution pattern of the substrates.